Study of IT Internet Target Architecture and Evolution Strategy of Telecom Enterprise - Man Li; Hongming Qiao; Wensheng Yao (Dianxin kexue)
The challenge faced by IT of the traditional telecom under the environment of internet was introduced,IT construction experience from the excellent internet company was referenced,and the differences of the business model,service characteristics and IT localization between the traditional telecom enterprises and the internet companies were analyzed.IT target architecture of internet model and evolution strategy of the telecom enterprise were proposed,and the related efforts which were needed for the evolution were analyzed.